2000
DOI: 10.1021/ef0001179
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Mn and Cu Mixed Oxides as Regenerable Sorbents for Hot Coal Gas Desulfurization

Abstract: Mixed oxides, prepared by calcination at 950 °C for 6 h of powder mixtures of manganese and copper oxides, have been studied as regenerable sorbents for hot coal gas desulfurization. For the stabilization of copper in the oxidation states 2+ or 1+ under strong reducing conditions of coal gas, different concentrations of component oxides have been used enhancing the formation of different mixed oxides. Copper was not stabilized by manganese oxides, but its presence in the fresh sorbent was completely necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…For the last few decades, much work had been concentrated on binary and ternary oxides for moderate-and high-temperature H 2 S removal, such as Zn-Mn [7], Cu-Mn [8], Fe-Mn [9], ZnFe 2 O 4 [10] and ZnTiO 3 [11]. Recently, cerium, a rare earth element of http lanthanide series, has received increasing attention due to its prominent oxygen storage capacity and unique redox couple Ce 3+ /Ce 4+ under oxidizing and reducing conditions, respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, much work had been concentrated on binary and ternary oxides for moderate-and high-temperature H 2 S removal, such as Zn-Mn [7], Cu-Mn [8], Fe-Mn [9], ZnFe 2 O 4 [10] and ZnTiO 3 [11]. Recently, cerium, a rare earth element of http lanthanide series, has received increasing attention due to its prominent oxygen storage capacity and unique redox couple Ce 3+ /Ce 4+ under oxidizing and reducing conditions, respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Slimane and Hepworth [14,15] also found that manganese-based sorbents presented high initial sorption rate, high sulfur capacity and good regenerative ability during hot coal gas desulfurization at 700-1000 • C but with high H 2 S equilibrium concentration (around 150 ppmv). Therefore, a variety of oxides, such as zinc oxide [16][17][18][19], iron oxides [18,[20][21][22], copper oxides [19,21,23,24], and vanadium oxides [25,26] were incorporated into manganese oxides in order to increase the H 2 S removal efficiency. However, the application of zinc and ferric oxides is limited to a maximum temperature of 600 • C due to zinc evaporation and the reduction of ferric oxides at reductive atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of zinc and ferric oxides is limited to a maximum temperature of 600 • C due to zinc evaporation and the reduction of ferric oxides at reductive atmosphere. The incorporation of copper oxides can enhance the dispersion of manganese oxides and improve the desulfurization performance of Mn-based adsorbents with H 2 S pre-breakthrough concentration of 50 ppmv [19,21,23,24]. Furthermore, copper oxides can also maintain its desulfurization ability at above 800 • C [5,27].…”
Section: Introductionmentioning
confidence: 99%
“…The spinel-type nanocrystals in both the dusts were considered to play an important role in sorbing H 2 S gas, referring to the studies on H 2 S sorptions of ZnFe 2 O 4 and CuMn 2 O 4 at elevated temperature. [17][18][19][20] The H 2 S sorptive capacities of Dusts-1 and -2 were, however, considerably low, compared with ZnFe 2 O 4 (Johnson Matthey, London, U.K.) and an Fe-based sorbent (Nissan Girdner Catalyst, Tokyo, Japan) on the market, whose H 2 S sorptive capacities were measured to be 0.29 and 0.27 g g −1 at room temperature, respectively. This was elucidated to be due to hardly any spinel-type nanocrystals in the inside of the SiO 2 matrix being available for H 2 S sorption.…”
Section: Resultsmentioning
confidence: 99%